A study of the disability impact among parents of mentally challenged children - Dr. V. Sunitha; Dr. Y. V. Siva Sankara Murty (Pediatric Review: International Journal of Pediatric Research, 2018)
Back ground: The child with mental retardation has special needs in addition to the regular needs of all children, and parents can find themselves over whelmed by various medical, care giving, financial and educational responsibilities. Government of India, “The National Policy on Mental Handicap”, has emphasized the importance of home-based care with parents as partners in the care process.Aim: To understand the positive and negative effects on parents of Mentally Retarded children by using National Institute for the Mentally Handicapped Disability Impact Scale (NIMH-DIS).Material and methods:Two intelligence tests [Vineland Social Maturity Scale (VSMS) and Developmental Screening Test (DST)] have been selected.Study sample is selected by purposive sampling method and categorized into three groups.Results: Parents of Mentally retarded children are impacted more by lifting & carrying the child (percentage of obtained score = 41.7), toileting (percentage ofobtained score = 40.6) and bathing (percentage of obtained score = 40). Maximum negative impact is on physical care (percentage of NIMH-DIS score = 35.5), followed by financial (percentage of NIMH-DIS score = 33.9) and loss of support (percentage of NIMH-DIS score = 33).Conclusion: It is not necessary for every parent having a Mental Retardation child to have negative impact but in some this can bring a positive impact, like acceptance of the situation realistically and standing right behind the Mental Retardation child to provide support.